Moderating effect of gender and age on the relationship between emotional intelligence with social and academic adjustment among first year university students - Ishak, Noor Azniza; Jdaitawi, Malek,T; Ibrahim, Yahya Saleh; Mustafa, Farid, T (Canadian Center of Science and Education, 2011)
This study examined whether emotional intelligence is significantly correlated with social adjustment and academic adjustment. It also explored the moderating effects of gender and age factors and their linked between emotional intelligence and social adjustment as well as academic adjustment among first year university students. 289 first year university students (148 males and 141 females) at the Irbid Govern Orate, North of Jordan, participate in the study and were categorized based on two age groups, younger students between the age of 18 – 25 and older students between the range of 26 and above. Two valid and reliable instruments were used to assess student’s emotional intelligence, social adjustment and academic adjustment. Correlation and multi-group analysis using structural equation model were used to analyse these data. The result shows no significant relationship between emotional intelligence and of both social adjustment and academic adjustment. In addition, the moderating effect of gender was not found. However, the moderating effect of age on the relationship between emotional intelligence with social adjustment and academic adjustment were established.